Answer:
3x - 1 = 6x - 7
x = 2
Explanation and Check part below
Hope this helps :)
Step-by-step explanation:
1. To solve it, first get the variable on same side.
3x - 1 = 6x - 7
- 3x - 3x
- 1 = 3x - 7
2. Isolate the variable by doing the inverse operation which is in this case addition (adding 7).
- 1 = 3x - 7
+ 7 + 7
6 = 3x
3. Isolate variable by doing the inverse operation which is in this case division (dividing by 3).
6 = 3x
3 3
2 = x
OR
x = 2
Check:
1. Substitute x with 2 and solve.
3(2) - 1 = 6(2) - 7
6 - 1 = 12 - 7
5 = 5
True statement.